LKS Pendekatan Saintifik dalam Meningkatkan KPS Konsep Laju Reaksi Berdasarkan Kemampuan Kognitif - Nadia Yolanda; Nina Kadaritna; Emmawaty Sofia (Jurnal Pendidikan dan Pembelajaran Kimia, 2017)
This research was aimed to describe effectiveness of student worksheets based on scientific approach on reaction rate concept to increase science process skills based-on cognitive ability. Samples of this research are XI IPA4 and XI IPA1 at SMA Negeri 13 Bandar Lampung. Method of research is Quasi Experimental with The Matching Only Pretest and Postest Control Group Design. Instruments used were student worksheets based-on scientific approach and conventional, pretest and postest questions. Data analysis techniques used were two path anova test and t-test. Result of research concluded are student worksheets based-on scientific approach was effective to increase science process skills students not only high cognitive ability students but also low cognitive ability students; implementation of student worksheets based-on scientific approach to increase science process skill are not influenced by cognitive ability; and increased of science process skill high cognitive ability students is not different as significant with low cognitive ability studentsPenelitian ini bertujuan untuk mendeskripsikan efektivitas LKS berbasis pendekatan saintifik dalam meningkatkan Keterampilan Proses Sains (KPS) pada konsep laju reaksi ditinjau dari kemampuan kognitif. Sampel dalam penelitian ini adalah kelas XI IPA4 dan kelas XI IPA1 di SMA Negeri 13 Bandar Lampung. Metode penelitian yang digunakan adalahQuasi EksperimentdenganThe Matching Only Pretest and Postest Control Group Design. Instrumen yang digunakan adalah LKS berbasis pendekatan saintifik dan konvensional, soal pretes dan postes. Teknik analisis data yang digunakan yaitu uji anova dua jalur dan uji-t. Hasil penelitian menyimpulkan LKS berbasis pendekatan saintifik efektif dalam meningkatkan KPS siswa baik siswa kemampuan kognitif tinggi maupun siswa kemampuan kognitif rendah; pembelajaran LKS berbasis pendekatan saintifik dalam meningkatkan KPS tidak dipengaruhi oleh kemampuan kognitif; dan peningkatan KPS siswa kemampuan kognitif tinggi tidak berbeda secara signifikan dengan siswa kemampuan kognitif rendah.Kata kunci: kemampuan kognitif, konsep laju reaksi, KPS, LKS berbasis pendekatan saintifik.